2017
DOI: 10.1074/jbc.m116.759811
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Nucleotide Binding Domain Dimers Rescues ABCC6 Mutants Associated with Pseudoxanthoma Elasticum

Abstract: Edited by Norma AllewellABC transporters are polytopic membrane proteins that utilize ATP binding and hydrolysis to facilitate transport across biological membranes. Forty-eight human ABC transporters have been identified in the genome, and the majority of these are linked to heritable disease. Mutations in the ABCC6 (ATP binding cassette transporter C6) ABC transporter are associated with pseudoxanthoma elasticum, a disease of altered elastic properties in multiple tissues. Although ϳ200 mutations have been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 59 publications
(100 reference statements)
2
14
0
Order By: Relevance
“…These mutants showed little to no fully glycosylated species and steady-state expression was reduced to less than 10%, when compared with the WT protein. The reduction in steady-state protein and lack of fully glycosylated species was consistent with ER-associated degradation, as previously described for processing mutants in ABCC6 (15,28). The R760W, V810M, and T811M mutants produced small amounts of fully glycosylated protein, although steady-state expression was markedly reduced compared with WT.…”
Section: Abcc6 Trafficking and Functionsupporting
confidence: 85%
See 3 more Smart Citations
“…These mutants showed little to no fully glycosylated species and steady-state expression was reduced to less than 10%, when compared with the WT protein. The reduction in steady-state protein and lack of fully glycosylated species was consistent with ER-associated degradation, as previously described for processing mutants in ABCC6 (15,28). The R760W, V810M, and T811M mutants produced small amounts of fully glycosylated protein, although steady-state expression was markedly reduced compared with WT.…”
Section: Abcc6 Trafficking and Functionsupporting
confidence: 85%
“…This could suggest a direct role for nucleotide during crystallization. Alternatively, the nucleotide may stabilize the free pool of NBD1 and prevent aggregation, as has been demonstrated for other NBDs, thereby indirectly facilitating crystallization (15,30,31). The adverse effects of the D777N, reported here, and D778N, previously reported, in the Walker B sequence suggest that Mg-ATP binding may be critical for the folding and/or structural stability of ABCC6 NBD1 (15).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Furthermore, systematic evaluation of a large library of ABCC6 mutations has identified mutations leading to altered protein folding and altered protein function. Preliminary data have also demonstrated that stabilization of mutant ABCC6, via specific domain-domain interactions, can facilitate proper trafficking and function of the mutant proteins, providing a mechanism for stabilization of the protein and rescue of the phenotype due to disease-causing mutations (Ran and Thibodeau, 2017). …”
Section: Animal Models Of Ectopic Mineralization Disordersmentioning
confidence: 99%